Investigating the effect of online consumer reviews on purchase intention among Gen Y and Z - Yuliana, Ade; Novandari, Weni; Setyawati, Sri Murni (Jurnal Siasat Bisnis, 2026)
Purpose – This research explains inconsistencies in research findings regarding the effect of online consumer reviews dimension (review timeliness, review quantity, review positive valence, review quality) and trust on purchase intentions, using a social influence theory approach.Design/methodology/approach – The sample in this study was 213 respondents, who were generation Y and generation Z, who had read online reviews of cosmetic products.Findings – The results reveal that online consumer reviews influence purchase intention primarily through the formation of consumer trust. Review quantity, review positive valence, and review quality have significant positive effects on trust and purchase intention, suggesting that consumers place greater importance on the credibility, positivity, and informativeness of review content when evaluating products online. Trust serves as an important mediating mechanism in transmitting the influence of review dimensions on purchase intention. Review timeliness does not exhibit a significant direct or indirect effect, suggesting that consumers usually rely more on the content and quality of reviews than on their recency when forming purchase intention. Research limitations/implications – This study has several limitations. The sample was dominated by Generation Z respondents, which may limit the generalizability of the findings across generations. The focus on cosmetic products also restricts the applicability of the results to other product categories. In addition, this study only examined four dimensions of online reviews and one mediating variable, namely trust. Future research is recommended to further explore the relationship between review timeliness and trust, as well as to include additional variables such as perceived credibility and consumer engagement.Practical implications – The managerial implication in this research is that online reseller should be able to encourage consumers to give positive reviews of their market offerings, because online consumer reviews can have an impact on increasing company sales.Originality/value – This study contributes to examine the social influence theory approachlinked to the dimensions of online reviews. It specifically focuses on generations Y and Z because these generations dominate the internet population and are more familiar with e-commerce than earlier generations. The value provided in this paper is that it is able to provide insight for companies and researchers in order to improve product reputation and explore future research.